Semantic Specificity in One-Year-Olds' Word Comprehension. Issue 4 (2nd October 2017) - Bergelson, Elika; Aslin, Richard
ABSTRACT: The present study investigated infants' knowledge about familiar nouns. Infants (n = 46, 12–20-month-olds) saw two-image displays of familiar objects, or one familiar and one novel object. Infants heard either a matching word (e.g. "foot' when seeing foot and juice), a related word (e.g. "sock" when seeing foot and juice) or a nonce word (e.g. "fep" when seeing a novel object and dog). Across the whole sample, infants reliably fixated the referent on matching and nonce trials. On the critical related trials we found increasingly less looking to the incorrect (but related) image with age. These results suggest that one-year-olds look at familiar objects both when they hear them labeled and when they hear related labels, to similar degrees, but over the second year increasingly rely on semantic fit. We suggest that infants' initial semantic representations are imprecise, and continue to sharpen over the second postnatal year.